Guidelines for The Preparation of Feasibility Reports for Industrial Projects - Planning Commission (Planning Commission, 1975)
The purpose of the information presented under the first two heads above is to provide a framework for evaluating individual projects. This framework would in effect be a partial corporate plan— it would specify the broad contours of growth of the industry concerned and the role of the enterprise submitting the feasibility report in it. This part of the exercise may be common to all the feasibility reports presented by the enterprise. However, generally even this part may have to be revised for each feasibility report as more information becomes available.
Planning Commission
Planning Commission